STRATEGI EKSPANSI GRAB DALAM MEMPENGARUHI PASAR TENAGA KERJA DI INDONESIA (2015-2020) - Richo Sunjaya (2022)
The entries of investment or FDI like multinational companies are certainly trying to make a profit. The goal is to gain profits in the host country and dominate the market by bringing up innovations that are needed by the community. The presence of multinational companies in developing countries is a mandate from the host country so that multinational companies can cultivate and employ as many people as possible in the host country. Even though the increasing number of workers from the labor market in the host country can help the wheels of the multinational company's economy turn, but the increasing number of workers also reduces the income of the multinational company. The entry of the multinational company Grab into Indonesia as a company engaged in the ride-hailing business has absorbed many workers in Indonesia. Many Indonesians consider working as a partner to the multinational company Grab as an answer to earn an income. The large number of workers absorbed by the multinational company Grab makes Grab must be able to strive to cultivate and develop the labor market in Indonesia which is in line with the innovations launched by Grab in order to meet the market needs of the people in Indonesia and earn profits. The innovation launched by Grab is seen from the theoretical point of view of Raymond Vernon Product Life Cycle (PLC) which contains four stages in developing the company's product innovations, and with the increasing number of innovations it can be aligned with the absorption of labor from the labor market so that innovation can run stably.